GAMBARAN PENGUASAAN KETERAMPILAN TEKNIK KOMUNIKASI DASAR KONSELING PASTORAL PADA MAHASISWA STKIP WIDYA YUWANA MADIUN, PROGRAM STUDI PENDIDIKAN AGAMA KATOLIK - Widodo, Bernardus (Widya Warta, 2021)
In the context of Pastoral Counseling services, mastery of basic communication technique skills is very important for a prospective pastoral officer to understand and master. The research objective was to describe the mastery of basic communication techniques skills in pastoral counseling and the benefits of supporting pastoral tasks. The research subjects were the fourth-semester students of STKIP Widya Yuwana Madiun in 2018/2019 who had passed the Pastoral Counseling course, totaling 37 students. From the results of the study, it could be concluded that the student's mastery of 13 basic technical skills of communication in pastoral counseling, 10 of them were good categories, with an average of 84.06%, namely the opening technique, structuring, attending, acceptance, reflection of feelings, exploration, confronting, questioning, reassurance and advice. Meanwhile, the other 3 techniques were categorized as not being sufficiently mastered by students, with an average of 66.67%, namely the techniques of reflection of meaning, restatement, and paraphrasing. Furthermore, in terms of usefulness, it showed that of the 15 randomly selected subjects, the pastoral counseling course was very useful and supportive for the task of pastoral care. Suggestions for development based on research results, namely the need for continuous sharpening and independent training so that students are more skilled in applying basic communication techniques for pastoral counseling. Â